Implementation of Mobile-Based Inventory Management System to Improve Stock Accuracy in SMEs - Harahap, Ricky Ramadhan; Supiyandi, Supiyandi; Rizal, Chairul (Jurnal Pengabdian Masyarakat Berdampak, 2026)
The SME partner faced significant issues with manual stock recording, resulting in discrepancies, delayed reporting, and input errors. This community service activity aimed to implement a mobile-based inventory management system to improve stock accuracy and operational efficiency. The methods included needs assessment, system design, cloud-based mobile deployment, training for 12 employees, and evaluation using the Stock Accuracy Rate and transaction recording time. The results showed an increase in stock accuracy from 83% to 96%, a reduction in stock discrepancies from 17% to 4%, and a decrease in recording time from 9 minutes to 3 minutes per transaction. The system enabled real-time reporting and automatic minimum stock notifications. The implementation significantly enhanced operational efficiency and data-driven decision-making.